A Deconstruction of Characters in “SpongeBob Movie: Sponge on the Run” - Eno Nur Hasanah; Norma Ita Sholichah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
This research discussed deconstruction of characters, which aimed to deconstruct a binary opposition between main character and minor character in SpongeBob Movie: Sponge on the Run. The researcher revealed other side of the characters having been not important in this movie becoming important because the minor characters formed a different character in the SpongeBob Movie: Sponge on the Run and figured out different character of SpongeBob. This researcher is based on Derrida's theory of deconstruction. A descriptive qualitative method in revealing data. There're two steps in deconstructing the text. The first is locating an opposition, and the second is determining which side is privileged. The researcher used note taking as an instrument to get valid data. Primary data in this study was taken from dialogue of the characters in